Design de interação para produto de aproximação entre marcas e influenciadores digitais - Paula , Helena Rodrigues de (2017)
The aim of this research is to gather information and inputs for the planning and development of a digital product (interface) that will be able to improve the relationships between digital influencers and brands. To achieve that goal, we used key concepts such as social networks, digital influencers, brands, interaction design and interface usability. We also studied a focus group composed by users of social networks who did not feel influenced by them. At the same time, we did semi-structured interviews with people that are influenced by social networks, in order to understand the behavior of these profiles. Finally, we took into account the behavior of digital influencers and their recruiters in order to understand the process of how the profile is chosen, as well as the recruitment, selection, follow-up and metrics, in order to identify their needs. Then, the collected data served as input for the creation of personas and scenarios that made it possible to draw a complete picture about the main user, which allowed us to design the tool. The materiality occurred through the product sitemap design, as well as the main streams and wireframes of the most important screens. The objective was improving the relationships between digital influencers and brands